Survivin expression in normal human bronchial epithelial cells: an early and critical step in tumorigenesis induced by tobacco exposure - Jin, Quanri (Oxford University Press, 2008)
The inhibitor of apoptosis protein survivin is selectively expressed in tumor cells. The tobacco component nicotine increases the transcription of the survivin gene in non-small cell lung cancer cells. However, the role of survivin expression induced by tobacco component is not clear during lung carcinogenesis. We investigated the effects of the tobacco components nicotine and its related carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) on survivin expression in normal human bronchial epithelial (NHBE) cells and examined the role of survivin in the malignant transformation of normal human bronchial epithelial (HBE) cells induced by these components. We found that survivin messenger RNA (mRNA) expression was detected in 41% (7 of 17) of bronchial brush specimens from heavy smokers. Nicotine and NNK increased survivin mRNA and protein expression levels in primary cultured NHBE cells and immortalized HBE cells. Bronchial epithelium in mice administered NNK also showed increased staining for survivin. Nicotine and NNK stimulated the Akt–mammalian target of rapamycin (mTOR) pathway in NHBE cells, leading to increased de novo synthesis of survivin protein. Induced survivin expression increased the survival potential of the cells, which was blocked by transfection with survivin-specific small interfering RNA (siRNA). siRNA-induced down-regulation of survivin expression also suppressed the tumorigenic potential of premalignant and malignant HBE cells exposed to the tobacco components. These findings suggest that NNK and nicotine induce survivin protein synthesis in NHBE cells by activating the Akt–mTOR pathway and thus blockade of the pathway effectively inhibits the tobacco-induced malignant transformation of HBE cells.